Unraveling monoclonal gammopathy of renal significance: a mini review on kidney complications and clinical insights - Shankar, Mythri; Yadla, Manjusha (Frontiers in Nephrology, 2024)
Monoclonal gammopathy of renal significance (MGRS) is where kidney injury occurs due to the accumulation or effects of abnormal monoclonal proteins. These proteins, originating from non-cancerous or pre-cancerous plasma cells or B cells, deposit in specific areas of the kidney. Mechanisms contributing to MGRS include high levels of vascular endothelial growth factor secretion, autoantibodies targeting complement components, and targeting specific receptors leading to nephropathy. Kidney lesions in monoclonal gammopathy of renal significance (MGRS) are classified based on the presence of organized or nonorganized deposits, including fibrillar, microtubular, or crystal inclusions. Kidney biopsy is essential for confirming the diagnosis of MGRS by identifying monoclonal immunoglobulin deposits. Immunofluorescence helps determine the class of light and/or heavy chain involved in MGRS. The treatment approach is clone-directed and hence it depends on the presence of B cell clone or plasma cell clone or any detectable monoclonal protein. Chemotherapy targeting plasma cell or B cell malignancies and autologous hematopoietic cell transplantation may be used to manage MGRS. Kidney outcomes in MGRS patients strongly correlate with the hematologic response to chemotherapy.